(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
In Africa, the use of poor and unhygienic methods for animal milking and milk processing that leads to spoilage of milk by microbes affects the production of milk and dairy products, especially in the small scale and local processing plants. This study was conducted to analyze the quality and safety of raw milk collected from six different towns in Kwami local government area of Gombe State, Nigeria. The samples were serially diluted using ten-fold dilution and used aliquot 1 ml to inoculate the appropriate media using pour plate technique. The total viable count for bacteria in CFU/ml on plate count agar (PCA) was highest in sample E from U/Anchau with an average of total viable count of 3.8x104 CFU/ml, followed by 3.0x104 CFU/ml in sample B (Dirri), then 2.8x104 CFU/ml in sample D from Burakosuma, 2.5x104 CFU/ml in sample F from Dun urji, 2.3x104 CFU/ml in sample C from Zanbe with least count from sample A at Bele as 1.8x104 CFU/ml. Five (5) bacterial species of public health importance were isolated and identified using biochemical tests namely; Enterobacter sp., Yersinia enterocolitica, Escherichia coli, Staphylococcus aureus and Salmonella sp.. Out of the organisms isolated, Enterobacter sp. had the highest occurrence of 93% (n=280), then Yersinia enterocolitica 90% (n=270), E. coli 70% (n=210), S. aureus 57% (n=170), and finally Salmonella sp. 23% (n=70). Based on the microbiological outcomes, preventive measures for milking and processing that focus on training of farmers and dairy employees for the improvement of the hygiene of local milk and dairy production chain should be defined.